2022
DOI: 10.3389/fvets.2022.871289
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Supplementation Improves the Subsequent Developmental Competence of Vitrified Porcine Zygotes

Abstract: Cryopreservation of embryos has been confirmed to cause oxidative stress as a factor responsible for impaired developmental competence. Currently, astaxanthin (Ax) raises considerable interest as a strong exogenous antioxidant and for its potential in reproductive biology. The present study aimed to investigate the beneficial effects of Ax supplementation during in vitro culture of vitrified porcine zygotes and the possible underlying mechanisms. First, the parthenogenetic zygotes were submitted to vitrificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…This indicates that increased lysosomal activity can be associated with induced autophagy as a survival response. Similar trends in mitochondrial and lysosomal activities were observed in porcine four-cell embryos and blastocysts after astaxanthin addition [42].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This indicates that increased lysosomal activity can be associated with induced autophagy as a survival response. Similar trends in mitochondrial and lysosomal activities were observed in porcine four-cell embryos and blastocysts after astaxanthin addition [42].…”
Section: Discussionsupporting
confidence: 75%
“…It is more likely that effects of AX on oocyte and embryo development vary depending on the concentration used. Thus, [42] described the accelerated formation of blastocysts from porcine zygotes vitrified after parthenogenesis as well as higher blastocyst rate at the concentration of 1.5 µM AX. Increased blastocyst rate after astaxanthin addition was also obtained in aging porcine oocytes [26].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the controls, rats that underwent AST treatment manifested increased levels of Beclin1 and LC3 and a decreased expression of p62 ( Abbaszadeh et al, 2022 ). Additionally, AST was shown to restore the normal function of lysosomes and notably inhibited the activation of mTOR complex1 ( Fu et al, 2022 ; Xiang et al, 2022 ), while this mechanism remains to be confirmed in SCI models.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be because it increases the concentration of intracellular reduced glutathione (GSH) and favors the concentrations of the enzyme glutathione peroxidase, essential for the embryonic oxidant balance [4]. This allows a decrease in ROS production, as has been observed in pigs, cattle, sheep, and goats [2,3,[5][6][7][8][9][10][11].…”
Section: Effect Of Resveratrol On Ivm DIV and Blastocyst Productionmentioning
confidence: 99%
“…Other antioxidants have been proven in porcine experiments, where Xiang et al [10] found that when adding 1.5 µM of astaxanthin to the culture medium the developmental competence of parthenogenetic zygotes improved (51.7% blastocysts). This concentration also improved the blastocyst formation rate of vitrified cloned zygotes (23.3% blastocysts).…”
Section: Introductionmentioning
confidence: 99%